Industry competition and non-GAAP disclosures - Isidro, H. (2021)
We examine the role of industry-level product market competition on non-GAAP disclosure decisions. We consider traditional measures of industry competition (concentration, price-cost margin, and set up costs), and large reductions in import tariff rates that identify an exogenous increase in competition. We find that competition intensity influences the likelihood of non-GAAP disclosure and the magnitude of non-GAAP exclusions. Our evidence suggests that strong competition encourages managers to disclose higher non-GAAP earnings. However, when competition is strong, firms with low performance relatively to the industry exclude smaller amounts. We also find that in competitive environments, managers are more likely to provide reconciliations and are less likely to exclude recurring items that are commonly excluded by other firms in the industry. These findings indicate that industry competition has a positive influence on the transparency of non-GAAP disclosures.